Grado mission - Spano, Carlo Christian, 1973- (carlochristianspano films, 2015)
The film chronicles some military activities carried out by the Italian contingent in Herat and Bala Morghab, Afghanistan.The film features 9 chapters with an ink on paper aphorism design.--